Preparation method of ternary metal acid catalyst
By doping Ce ions in the CuMn2O4 spinel catalyst and forming the SO42-/CuxCe1-xMn2O4 acid catalyst, the problem of high cost and toxic by-products when treating high-salt-containing refining concentrated water is solved, and the effect of efficient degradation of phenol is achieved.
Patent Information
- Application Number
- CN202411856058.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-17
AI Technical Summary
The existing electrochemical advanced oxidation technology needs to operate within the pH range of 2 to 4 when treating high salt-containing refining concentrated water, which is costly and may produce toxic chlorine by-products.
Using the preparation method of ternary metal acid catalyst, the SO42-/CuxCe1-xMn2O4 acid catalyst is formed by doping Ce ions in the CuMn2O4 spinel catalyst and chelating it through sulfuric acid, which is used to catalyze the degradation of phenol by ozone micro-nano bubbles.
This method efficiently degrades phenol in water without additional adjustment of the pH of the water, and does not produce chlorinated by-products, reducing treatment costs and improving treatment efficiency.
Smart Images

Figure CN119680587A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of deep treatment of refining concentrated water, and in particular to a method for preparing a ternary metal acid catalyst. Background Art
[0002] The wastewater generated by the refining industry is characterized by high salt, high ammonia nitrogen, and high oil pollution. The main pollutants in the concentrated water produced after the membrane treatment of the wastewater in the refining industry are petroleum organic matter, including phenols, aldehydes, aromatic hydrocarbons, sulfur-containing and nitrogen-containing compounds, etc. At present, the treatment of refined concentrated water mainly adopts ultrafiltration membrane-reverse osmosis membrane double membrane system circulation treatment, multiphase photocatalytic oxidation technology, ozone oxidation catalytic technology, electrocatalytic oxidation technology, and Fenton reagent method. Oxidation and reduction reactions occur simultaneously during the photocatalytic oxidation process. Photogenerated holes can not only oxidize OH adsorbed on the surface of the semiconductor, but also reduce the ions in the electrolyte. - and H2O to generate highly oxidizing ·OH, which eventually degrades organic matter into CO2 and H2O. However, photocatalysis is unstable and too expensive when used on a large scale. The application of electrochemical advanced oxidation to treat high-salt refining concentrated water can bring out its many advantages, such as improving conductivity, reducing reaction energy consumption, mild reaction conditions, and easy integration with the operating unit of the next module.
[0003] However, there are still some problems in the large-scale industrial application of electrochemical advanced oxidation technology. First, electrochemical oxidation technology needs to be carried out in a pH range (2-4) to effectively treat wastewater. Since most high-salt refining wastewater is medium-alkaline wastewater, adding acid to adjust the pH will increase costs. Second, when using anodic oxidation technology to treat wastewater containing high concentrations of chloride ions, chloride ions will be oxidized at the anode into chlorine-containing active substances such as Cl2 and HOCl. - etc. are further transformed into toxic and harmful chlorinated by-products. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing a ternary metal acid catalyst, which can efficiently degrade phenol in water without additionally adjusting the pH of the water body and will not produce chlorinated byproducts.
[0005] In one aspect of the present invention, the present invention provides a method for preparing a ternary metal acid catalyst. According to an embodiment of the present invention, on the basis of preparing a CuMn2O4 spinel catalyst, cerium ions are added to dope Ce in the CuMn2O4 spinel catalyst to form a ternary metal catalyst, and then chelate sulfate to form SO4 2- / Cu x Ce 1-x The Mn2O4 type acid catalyst is the ternary metal acid catalyst.
[0006] In addition, the method for preparing a ternary metal acidic catalyst according to the above embodiment of the present invention may also have the following additional technical features:
[0007] In some embodiments of the present invention, the method comprises the following steps:
[0008] (1) fully mixing nitrates containing Cu, Mn, and Ce in an aqueous solution, and heating the solution to 40 to 50° C. to obtain a metal nitrate solution;
[0009] (2) adding the citric acid solution dropwise to the metal nitrate solution, adjusting the pH of the mixed solution with an ammonia solution, heating the solution to 70-80° C. and stirring at a constant temperature to evaporate the aqueous solution until a colloid is formed;
[0010] (3) drying the colloid to form a fluffy solid, performing a first calcination, grinding the calcined powder thoroughly, and immersing it in a sulfuric acid or ammonium sulfate solution;
[0011] (4) Drying the impregnated catalyst and performing a second calcination to obtain the ternary metal acidic catalyst.
[0012] In some embodiments of the present invention, in step (1), the molar ratio of Cu, Mn and Ce is 1-x:1.5:x, wherein x=0.05-0.2.
[0013] In some embodiments of the present invention, in step (2): the molar ratio of metal ions to citric acid is 1.5 to 2:1; the ammonia solution is composed of deionized water and 25% ammonia water in a volume ratio of 1:1, and the pH of the mixed solution is adjusted to alkaline by adding ammonia solution.
[0014] In some embodiments of the present invention, in step (3): the colloid drying temperature is 50-60°C, and the drying time is 2-3h; the first calcination temperature is 600-800°C, the calcination time is 4-5h, and the heating rate is 1-5°C / min; the impregnation time is 1-2h, and the solid-liquid ratio of the impregnation is 1:15-20.
[0015] In some embodiments of the present invention, in step (4): the impregnated catalyst is dried at a temperature of 60-80°C for 1-2 hours; the second calcination temperature is 500-600°C for 2-3 hours, and the heating rate is 1-2°C / min.
[0016] In another aspect of the present invention, the present invention provides a ternary metal acidic catalyst prepared according to the preparation method of the ternary metal acidic catalyst.
[0017] In another aspect of the present invention, the present invention provides a use of a ternary metal acid catalyst. According to an embodiment of the present invention, the ternary metal acid catalyst is used to catalyze the degradation of the pollutant phenol by ozone micro-nano bubbles.
[0018] In addition, the use of a ternary metal acid catalyst according to the above embodiment of the present invention may also have the following additional technical features:
[0019] In some embodiments of the present invention, the concentration of ozone is maintained at 0.3-1 mg / L, the gas flow rate of ozone is 0.16-1.2 L / min; the dosage of the ternary metal acid catalyst is 500-1000 mg of catalyst per liter of waste liquid; and the concentration of the pollutant phenol is 10-40 mg / L.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] 1) The present invention uses the sol-gel method to prepare high-purity CuMn2O4 copper-manganese spinel. Under this preparation condition, the amount of Cu ions added is reduced appropriately, and an equal amount of Ce ions are added at the same time to dope Ce in CuMn2O4, forming more oxygen vacancies and surface defects, thereby improving the catalyst's adsorption capacity for pollutants. At the same time, it provides sites for surface acidification to chelate with sulfuric acid, chelating sulfate to form SO4 2- / Cu x Ce 1-x Mn2O4 type acid catalyst forms Lewis and Bronsted acid sites to promote the quenching of ozone micro-nano bubbles to produce hydroxyl radicals. At the same time, the interaction between Cu, Mn and Ce ions can catalyze ozone to produce hydroxyl radicals with high oxidizing ability, thereby efficiently degrading phenol in water.
[0022] 2) The preparation process of the copper-manganese-cerium ternary acid catalyst is simple, easy to operate, and the catalyst preparation cycle is short. It has potential application prospects in the treatment of concentrated water in the petroleum industry.
[0023] 3) The ternary metal acid catalyst contacts ozone micro-nano bubbles in water, promoting the quenching of bubbles to produce hydroxyl radicals. In addition, the ozone inside the bubbles will also be catalyzed by the catalyst to produce hydroxyl radicals ·OH after being released, which has great application prospects in the treatment of wastewater containing organic matter.
[0024] 4) Most high-salt refining wastewater is moderately alkaline, and ozone micro-nano bubble technology can efficiently degrade pollutants under a wide range of pH environments. In particular, in an alkaline environment, it is more conducive to the chain reaction of ozone micro-nano bubbles catalyzed by the catalyst, generating a large amount of ·OH in the system, eliminating the cost increase caused by the need to add acid to adjust the pH in other technologies.
[0025] 5) The use of copper-manganese-cerium ternary acid catalyst to catalyze ozone micro-nano bubbles will not produce toxic and harmful by-products such as Cl2 and HOCl - The entire degradation process is safe and green, and will not cause secondary pollution or harm. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The X-ray diffraction patterns of CuMn2O4 prepared from the nitrate mixed solution in Example 1 of the present invention at pH=6, 7, 8, and a molar ratio of Cu ions to Mn ions of 1:2;
[0027] Figure 2 The X-ray diffraction patterns of CuMn2O4 prepared when the nitrate mixed solution in Example 1 of the present invention is at pH=6, 7, 8, and the molar ratio of Cu ions to Mn ions is 1:1.5;
[0028] Figure 3 The X-ray diffraction diagram of CuMn2O4 prepared in Example 1 of the present invention is shown when the nitrate mixed solution is at pH = 7 and 8, and the molar ratio of Cu ions to Mn ions is 1:1.5 and 1:1;
[0029] Figure 4 The FTIR curve of the CuMn2O4 catalyst obtained after calcination at 700°C for 4h at a metal ion molar ratio of Cu:Mn=1:1.5 and pH=8 in Example 1 of the present invention, and the SO4 2- FTIR curve of the Cu / CuMn2O4 catalyst, the reduction of x=0.15 mol of Cu ions in Example 3, and the corresponding doping of an equal amount of x=0.15 mol of Ce ions to prepare Cu 0.85 Ce 0.15 Mn2O4 catalyst, then sulfated and calcined to obtain SO4 2- / Cu 0.85 Ce 0.15 FTIR curve of Mn2O4 catalyst, similarly, the Cu ions are reduced by x = 0.05 ~ 0.2 mol, and the Cu ions are prepared by doping with the same amount of Ce ions x = 0.05 ~ 0.2 mol 1-x Ce x Mn2O4 catalyst, then sulfation to obtain the ternary acid catalyst SO4 2- / Cu x Ce 1-x FTIR curve of Mn2O4;
[0030] Figure 5 SO4 is the ternary metal catalyst in Examples 3 and 4 of the present invention after being impregnated with sulfuric acid or ammonium sulfate 2- / Cu 0.85Ce 0.15 Pyridine infrared detection image of Mn2O4;
[0031] Figure 6 NH3-TPD is used to quantitatively analyze SO4 in Example 5 of the present invention 2- / Cu 0.85 Ce 0.15 Mn2O4 surface acidity;
[0032] Figure 7 The degradation of phenol wastewater by using air micro-nano bubbles, the degradation of phenol wastewater by using ozone micro-nano bubbles alone, and the degradation of phenol wastewater by using SO4 2- / Cu 0.85 Ce 0.15 Energy efficiency diagram of phenol wastewater degradation using Mn2O4 catalyst in collaboration with ozone micro-nano bubbles. DETAILED DESCRIPTION
[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Example 1
[0035] The preparation method of CuMn2O4 comprises the following steps:
[0036] (1) Cu 2+ :Mn 2+ =1:2, 1:1.5, 1:1, 1.5:1 ratios were fully stirred and dissolved in 50 mL of deionized water;
[0037] (2) The molar ratio of citric acid to metal ions is 1:1. Dissolve citric acid in 25 ml of water and then add it dropwise to the metal ion mixed solution while maintaining high-speed stirring;
[0038] (3) The pH of the mixed solution was adjusted to 6, 7, or 8 using diluted (1:1) ammonia water, and the mixture was continuously stirred using a constant temperature magnetic stirrer. After the temperature was raised to 80° C., the aqueous solution was evaporated at a constant temperature until the precursor solution was transformed into a viscous green colloid.
[0039] (4) The colloid was first transferred to an oven for drying and then placed in a muffle furnace for calcination at 700 °C for 4 h.
[0040] Depend on Figures 1 to 3As shown in the figure, by comparing the XRD patterns under different conditions, high-purity CuMn2O4 can be obtained in the sample after calcination at 700℃ for 4h at a metal ion molar ratio of Cu:Mn=1:1.5, pH=8, and avoiding the presence of CuO and Mn2O3 in the sample. The subsequent catalyst preparation is based on this condition.
[0041] Example 2
[0042] SO4 2- / The preparation method of CuMn2O4 catalyst comprises the following steps:
[0043] (1) According to the method of Example 1, the parameter conditions are as follows: at a metal ion molar ratio of Cu:Mn=1:1.5, pH=8, calcination at 700°C for 4h, a high-purity CuMn2O4 catalyst is prepared;
[0044] (2) The CuMn2O4 catalyst powder was immersed in 1 mol / L sulfuric acid with a solid-liquid ratio of 1:15 for 1 h and then placed in an oven at 80°C to dry.
[0045] (3) The dried powder of step (2) is transferred to a muffle furnace for calcination at a concentration of 600°C for 3 hours at a heating rate of 2°C / min, and then naturally cooled to room temperature to complete the acidic metal catalyst SO4 2- / Preparation of CuMn2O4.
[0046] Example 3
[0047] The method for preparing a copper-manganese-cerium ternary acid catalyst comprises the following steps:
[0048] (1) Weigh 2.054 g of Cu(NO3)2·3H2O, dissolve it in 25 mL of deionized water, and stir it on a thermostatic magnetic stirrer until the solid is completely dissolved;
[0049] (2) Weigh 5.368 g of Mn(NO3)250 wt%, and stir evenly with 25 mL of deionized water to obtain a clear solution;
[0050] (3) Weigh 0.651 g of Ce(NO3)3·6H2O, dissolve it in 25 mL of deionized water, and stir it on a thermostatic magnetic stirrer until the solid is completely dissolved;
[0051] (4) Weigh 3 g of citric acid, dissolve it in 25 mL of deionized water, and stir it on a constant temperature magnetic stirrer until the solid is completely dissolved;
[0052] (5) Mix the solutions of steps (1), (2) and (3), raise the temperature to 50°C, maintain for 30 min, and stir vigorously at 600 r / min;
[0053] (6) At a solution temperature of 50° C. and a speed of 600 r / min, the citric acid solution of step (4) was added dropwise to the solution of step (5).
[0054] (7) diluting 25% ammonia water (volume ratio of ammonia water to deionized water is 1:1), and adding the diluted ammonia water dropwise to the solution in step (6), and adjusting the pH value of the solution to 8;
[0055] (8) The temperature of the solution in step (7) was raised to 80° C., maintained at a constant temperature, and stirred vigorously at 800 rpm for 2 h to form a viscous colloid with poor fluidity.
[0056] (9) The viscous colloid was transferred to an oven at 60 °C and dried for 2 h to form a fluffy porous solid.
[0057] (10) The fluffy porous solid was ground into powder and transferred to a muffle furnace for calcination at a temperature of 700 °C for 4 h. The temperature rise rate of the muffle furnace was 2 °C / min. The solid was then naturally cooled to room temperature to complete the preparation of the copper-manganese-cerium ternary metal catalyst. The catalyst was rinsed with deionized water and then dried.
[0058] (11) The copper-manganese-cerium ternary metal catalyst powder of step (10) was immersed in 1 mol / L sulfuric acid with a solid-liquid ratio of 1:15 for 1 hour, and then placed in an oven at 80° C. to dry.
[0059] (12) The dried powder of step (11) is transferred to a muffle furnace for calcination at a concentration of 600°C for 3 hours at a heating rate of 2°C / min, and then naturally cooled to room temperature to complete the copper-manganese-cerium ternary acidic metal catalyst SO4 2- / Cu 0.85 Ce 0.15 Preparation of Mn2O4.
[0060] Similarly, preparation Figure 4 Medium series SO4 2- / Cu 1-x Ce x Mn2O4 (x = 0.05, 0.1, 0.2) catalyst, firstly add metal salt according to steps (1) to (3) with a molar ratio of Cu:Ce:Mn = 1-x:x:1.5, then prepare SO4 in the corresponding proportion according to steps (4) to (12) 2- / Cu 1-x Ce x Mn2O4 catalyst.
[0061] like Figure 4 As shown in the figure, the spinel phase is well preserved after modification without being destroyed, and the -1The presence of S=O was detected at the catalyst surface, proving that metal ions and sulfate ions were chelated and SO4 2- .
[0062] Example 4
[0063] The method for preparing a copper-manganese-cerium ternary acid catalyst comprises the following steps:
[0064] (1) Accurately weigh 2.054 g of Cu(NO3)2·3H2O, dissolve it in 25 mL of deionized water, and stir it on a thermostatic magnetic stirrer until the solid is completely dissolved;
[0065] (2) Accurately weigh 5.368 g of Mn(NO3)250 wt%, and stir evenly with 25 mL of deionized water to obtain a clear solution;
[0066] (3) Accurately weigh 0.651 g of Ce(NO3)3·6H2O, dissolve it in 25 mL of deionized water, and stir it on a constant temperature magnetic stirrer until the solid is completely dissolved;
[0067] (4) Accurately weigh 3 g of citric acid, dissolve it in 25 mL of deionized water, and stir it on a constant temperature magnetic stirrer until the solid is completely dissolved;
[0068] (5) Mix the solutions of steps (1), (2) and (3), raise the temperature to 50°C, maintain for 30 min, and stir vigorously at 600 r / min;
[0069] (6) At a solution temperature of 50° C. and a speed of 600 r / min, the citric acid solution of step (4) was added dropwise to the solution of step (5).
[0070] (7) diluting 25% ammonia water (volume ratio of ammonia water to deionized water is 1:1), and adding the diluted ammonia water dropwise to the solution in step (6), and adjusting the pH value of the solution to 8;
[0071] (8) The temperature of the solution in step (7) was raised to 80° C., maintained at a constant temperature, and vigorously stirred at 800 rpm for 2 h to form a viscous colloid with poor fluidity.
[0072] (9) The colloid was transferred to an oven at 60 °C and dried for 2 h to form a fluffy porous solid.
[0073] (10) The dried solid was ground into powder, transferred to a muffle furnace for calcination at a temperature of 700 °C, a calcination time of 4 h, a heating rate of 2 °C / min, and then naturally cooled to room temperature, thereby completing the preparation of the copper-manganese-cerium ternary metal catalyst. The catalyst was rinsed with deionized water and then dried.
[0074] (11) The catalyst powder was immersed in 1.5 mol / L ammonium sulfate. 10 ml of ammonium sulfate solution was used for every 1 g of catalyst for 2 h. After the immersion, the catalyst powder was placed in an oven at 80 °C for drying.
[0075] (12) The dried powder of (11) was transferred to a muffle furnace for calcination at a concentration of 600°C for 3 h. The temperature rise rate of the muffle furnace was 2°C / min, and then naturally cooled to room temperature. The copper-manganese-cerium ternary acidic metal catalyst SO4 was completed. 2- / Cu 0.85 Ce 0.15 Preparation of Mn2O4.
[0076] like Figure 5 As shown, at 1490m -1 A characteristic peak was detected at , which is the common binding site of Lewis acid and Bronsted acid.
[0077] Example 5
[0078] like Figure 6 As shown, the ternary metal acid catalyst SO4 prepared in Example 3 2- / Cu 0.85 Ce 0.15 Mn2O4 shows desorption peaks of NH3 molecules in the temperature range of 100-700℃, and these desorption regions are divided into peak I (100-200℃), peak II (400-500℃) and peak III (630-700℃), which belong to the NH3 desorption peaks of physical adsorption, weak acid and medium-strong acid sites, respectively.
[0079] Example 6
[0080] The ternary metal acid catalyst SO4 prepared in Example 3 was used 2- / Cu 0.85 Ce 0.15 The degradation of pollutant phenol by Mn2O4-catalyzed ozone micro-nano bubbles includes the following steps:
[0081] Gas-liquid mixing pump liquid flow rate = 1m 3 / L, the water inlet pressure of the micro-nano bubble generator is 40Mpa, the gas flow rate is 120mL / min, the ozone concentration is 0.4mg / L, and the gas-liquid ratio is 1:17. Add SO4 2- / Cu 0.85 Ce 0.15 The Mn2O4 catalyst is 500 mg / L, and microwave ultrasound is used to evenly disperse the catalyst in the solution.
[0082] Air micro-nano bubbles and ozone micro-nano bubbles were used as the control group. The generation condition of air micro-nano bubbles was as follows: the liquid flow rate of the gas-liquid mixing pump = 1m3 / L, water inlet pressure of micro-nano bubble generator is 40Mpa, air flow rate is 120mL / min, gas-liquid ratio is 1:17. The generation conditions of ozone micro-nano bubbles are gas-liquid mixing pump liquid flow rate = 1m 3 / L, the water inlet pressure of the micro-nano bubble generator is 40Mpa, the gas flow rate is 120mL / min, the ozone concentration is 0.4mg / L, and the gas-liquid ratio is 1:17.
[0083] In the experiment, a 40 mg / L phenol solution was prepared, the reaction temperature was maintained at 25°C, water samples were taken at set time points, and the phenol concentration was tested using a UV spectrophotometer.
[0084] from Figure 7 It can be seen that air micro-nano bubbles have no degradation effect on phenol. When ozone micro-nano bubbles are used alone to degrade phenol, the removal rate can reach 75%, which can reduce SO4 2- / Cu 0.85 Ce 0.15 After the Mn2O4 catalyst was introduced into the system, the degradation rate could reach over 90%, and the removal effect of phenol was improved by 15%.
[0085] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the present invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A method for preparing a ternary metal acidic catalyst, characterized in that: On the basis of preparing CuMn2O4 spinel catalyst, cerium ions are added to dope Ce into the CuMn2O4 spinel catalyst to form a ternary metal catalyst, which then chelates sulfate to form SO4 2- / Cu x Ce 1-x The Mn2O4 type acid catalyst is the ternary metal acid catalyst.
2. The method for preparing a ternary metal acidic catalyst according to claim 1, characterized in that: The following steps are involved: (1) fully mixing nitrates containing Cu, Mn, and Ce in an aqueous solution, and heating the solution to 40 to 50° C. to obtain a metal nitrate solution; (2) adding the citric acid solution dropwise to the metal nitrate solution, adjusting the pH of the mixed solution with an ammonia solution, heating the solution to 70-80° C. and stirring at a constant temperature to evaporate the aqueous solution until a colloid is formed; (3) drying the colloid to form a fluffy solid, performing a first calcination, grinding the calcined powder thoroughly, and immersing it in sulfuric acid; (4) Drying the impregnated catalyst and performing a second calcination to obtain the ternary metal acidic catalyst.
3. The method for preparing a ternary metal acidic catalyst according to claim 2, characterized in that: In the step (1), the molar ratio of Cu, Mn and Ce is 1-x:1.5:x, wherein x=0.05-0.
2.
4. The method for preparing a ternary metal acidic catalyst according to claim 2, characterized in that: In the step (2): The molar ratio of metal ions to citric acid is 1.5 to 2:1; The ammonia solution consists of deionized water and 25% ammonia water in a volume ratio of 1:1, and the pH of the mixed solution is adjusted to alkaline by dropping the ammonia solution.
5. The method for preparing a ternary metal acidic catalyst according to claim 2, characterized in that: In the step (3): The colloid drying temperature is 50-60°C and the drying time is 2-3h; The temperature of the first calcination is 600-800°C, the calcination time is 4-5h, and the heating rate is 1-5°C / min; The immersion time is 1 to 2 hours, and the solid-liquid ratio of the immersion is 1:15 to 20.
6. The method for preparing a ternary metal acidic catalyst according to claim 2, characterized in that: In the step (4): The drying temperature of the impregnated catalyst is 60-80°C and the drying time is 1-2h; The temperature of the second calcination is 500-600°C, the calcination time is 2-3h, and the heating rate is 1-2°C / min.
7. A ternary metal acidic catalyst prepared according to the preparation method of the ternary metal acidic catalyst according to any one of claims 1 to 6.
8. Use of the ternary metal acid catalyst according to claim 7, characterized in that: The ternary metal acid catalyst is used for catalyzing ozone micro-nano bubbles to degrade the pollutant phenol.
9. The use of a ternary metal acid catalyst according to claim 8, characterized in that: The concentration of ozone is 0.3-1 mg / L, and the gas flow rate of ozone is 0.16-1.2 L / min; The dosage of the ternary metal acid catalyst is 500-1000 mg per liter of wastewater; The concentration of the pollutant phenol is 20-40 mg / L.
Citation Information
Patent Citations
Two-stage micro / nano aeration and catalytic ozonation wastewater treatment system
CN104710002A
Mn / Ce / Cu-based low-temperature plasma catalyst as well as preparation and application
CN108940304A
Method for preparing spinel type catalyst for catalytic combustion of VOCs under assistance of low-temperature plasma
CN111905714A
Method for degrading bisphenol A in water based on manganese oxide modified copper-manganese spinel
CN113772802A
Multi-stage circulation catalytic ozonation reaction device and catalytic oxidation method
CN113908777A